Deletion of Estrogen Receptor Beta in Osteoprogenitor Cells Increases Trabecular but Not Cortical Bone Mass in Female Mice. (13th October 2015) - Nicks, Kristy M; Fujita, Koji; Fraser, Daniel; McGregor, Ulrike; Drake, Matthew T; McGee‐Lawrence, Meghan E; Westendorf, Jennifer J; Monroe, David G; Khosla, Sundeep
ABSTRACT: Although the role of ERα in regulating bone metabolism has been extensively studied, ERβ has been largely dismissed as a relevant modulator of bone mass. Previous studies examining ERβ utilized a germline knockout mouse expressing transcript variants of ERβ and displaying systemic hormonal changes that confounded interpretation of the skeletal phenotype. Thus, we used a conditional ERβ mouse model to achieve deletion of ERβ specifically in early osteoprogenitor cells using the Prx1‐Cre driver. We observed marked increases in the trabecular bone volume fraction (of 58% [ p  < 0.003] and 93% [ p  < 0.0003] in 6‐ and 12‐week‐old female ERβ Prx1–CKO mice, respectively) but no changes in cortical bone. Serum estradiol and IGF‐I levels were unaltered in ERβ Prx1–CKO mice. Bone formation and resorption indices by histomorphometry and serum assays were unchanged in these mice, suggesting that alterations in bone turnover may have occurred early in development. However, the ratio of colony‐forming unit‐osteoblasts (CFU‐OBs) to CFU‐fibroblasts (CFU‐Fs) was increased in bone marrow cultures from ERβ Prx1–CKO compared with control mice, indicating increased differentiation of osteoblast precursor cells into osteoblasts in ERβ Prx1–CKO mice. Detailed quantitative polymerase chain reaction analyses of 128 genes in 16 prespecified pathways revealed significant downregulation of 11 pathways in ERβ Prx1–CKO mice. Thus, deletion of ERβ specifically in osteoblast lineage cells, in the absence of all splice variants, increases trabecular bone mass and modulates multiple pathways related to bone metabolism. These findings suggest that pharmacological inhibition of ERβ in bone may provide a novel approach to treat osteoporosis. © 2015 American Society for Bone and Mineral Research.